2005
DOI: 10.4049/jimmunol.175.5.2868
|View full text |Cite|
|
Sign up to set email alerts
|

Critical Role for CD103+CD8+ Effectors in Promoting Tubular Injury following Allogeneic Renal Transplantation

Abstract: Immune destruction of the graft renal tubules is an important barrier to the long-term function of clinical renal allografts, but the underlying mechanisms remain obscure. CD103—an integrin conferring specificity for the epithelial cell-restricted ligand, E-cadherin—defines a subset of CD8 effectors that infiltrate the graft tubular epithelium during clinical rejection episodes, predicting a causal role for CD103+CD8+ effectors in tubular injury. In the present study, we used rodent transplant models to direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…There are some limitations to all these models, leaving open the question of whether the effector mechanisms are model specific, differing between islet and solid organ transplantation. A recent study (23) investigating the role of CD103 + CD8 + effector cells in rat kidney allografts, using a monoclonal antibody to CD103 to reduce accumulation of CD8 + cells in the graft, also concluded that CD103 was not essential for tubulitis or tubular injury, Histology, E-cadherin staining and tubular surface area in normal kidneys (NCBA), isografts and allografts rejecting in wild-type hosts (WT) or in hosts lacking granzyme A and B (GzmAB −/− ) or perforin (Prf −/− ) at day 21 1 1 E-cadherin staining was scored as the percentage of tubules in the cortex area with positive staining (<25%: 1; 25-75%: 2; >75%: 3); staining intensity was scored as weak (1), intermediate (2) or strong (3). Separate scores were obtained for staining of the basolateral or apical membrane.…”
Section: Loss Of Cadherins In Kidney Allograft Rejectionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are some limitations to all these models, leaving open the question of whether the effector mechanisms are model specific, differing between islet and solid organ transplantation. A recent study (23) investigating the role of CD103 + CD8 + effector cells in rat kidney allografts, using a monoclonal antibody to CD103 to reduce accumulation of CD8 + cells in the graft, also concluded that CD103 was not essential for tubulitis or tubular injury, Histology, E-cadherin staining and tubular surface area in normal kidneys (NCBA), isografts and allografts rejecting in wild-type hosts (WT) or in hosts lacking granzyme A and B (GzmAB −/− ) or perforin (Prf −/− ) at day 21 1 1 E-cadherin staining was scored as the percentage of tubules in the cortex area with positive staining (<25%: 1; 25-75%: 2; >75%: 3); staining intensity was scored as weak (1), intermediate (2) or strong (3). Separate scores were obtained for staining of the basolateral or apical membrane.…”
Section: Loss Of Cadherins In Kidney Allograft Rejectionmentioning
confidence: 98%
“…+ effector cells in rat kidney allograft rejection found that treatment with a monoclonal antibody to CD103 reduced accumulation of CD8 + cells in graft renal tubules and attenuated tubular injury in cyclosporine-treated rats (23). In contrast, in rats with a fully functional immune system, i.e.…”
Section: Cd8mentioning
confidence: 99%
“…Expression of ␣ E (CD103)␤ 7 appears to be associated with cytotoxic activity of CD8 ϩ T cells in graft-versus-host disease and allogeneic transplantation. 19,20 Along this line, interactions of ␣ E (CD103)␤ 7 with E-cadherin are crucial for lysis of E-cadherin ϩ tumor cells by cytotoxic T cells in some cases. 21 Moreover, expression of ␣ E (CD103)␤ 7 is associated with several important cellular activities such as antigen presentation 22 or stimulation of T reg 23 and some mucosal CD8 ϩ T cells 24,25 by ␣ E (CD103)␤ 7 ϩ dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that CD103 plays an essential role in TCR-dependent tumor-cell killing through interaction with its ligand, the epithelial cell marker E-cadherin on target cells (6). This integrin has also been associated with the cytotoxicity of CD8 þ T cells in several pathologies, including graft-versus-host disease (GVHD; 7), allogeneic transplant rejection (8)(9)(10), and autoimmune diseases (11,12). CD103 is frequently expressed on intraepithelial lymphocytes (IEL; 13) as well as on a subpopulation of CD3 þ / CD8 þ TIL (6,(14)(15)(16), CD4 þ /CD25 þ Treg cells (17), and dendritic cells (18).…”
Section: Introductionmentioning
confidence: 99%